Effect of thickness on structural properties of BixSb2-xTe3 thin films - Hussain. M. Selman (Iraqi Journal of Physics, 2019)
BixSb2-xTe3 alloys with different ratios of Bi (x=0, 0.1, 0.3, 0.5, and 2) have been prepared, Thin films of these alloys were prepared using thermal evaporation method under vacuum of 10-5 Torr on glass substrates at room temperature with different deposition rate (0.16, 0.5, 0.83) nm/sec for thickness (100, 300, 500) respectively. The X–ray diffraction measurements for BixSb2-xTe3 bulk and thin films indicate the polycrystalline structure with a strong intensity of peak of plane (015) preferred orientation with additional peaks, (0015) and (1010 ) reflections planes, which is meaning that all films present a very good texture along the (015) plane axis at different intensities for each thin film for different thickness. AFM measurements for the thin films of BixSb2-xTe3, show that the grain size and the average surface roughness decreases with increasing of the percentage Bi for different thickness.